TERMINATION OF RIGHT TO PREVENTIVE MEASURES - RADU MARIUS (Challenges of the Knowledge Society, 2012)
Preventive measures were binding, without, however, being procedural criminal sanctions or penalties and not run counter to the freedom of the individual and does not attack the principle of presumption of innocence. They ensure the good running of the criminal process, which has led to the inclusion of modern legislation in all imprisonment by way of judicial review, as a procesuala of the most severe.Termination of right to preventive measures shall designate by virtue of which the legal situation, whether in judicial activities involved some "incident" which recognizes ope legis effect subject to extinctive interpretation towards preventive measures, judicial bodies are required to cease such action.The judicial authority is obliged, therefore, to release the detained or arrested when there is one of the situations referred to in article 140 from the code of penal procedure.This study has proceeded from the need to standardise and judicial practice and the consistent application of the law in the matter of the termination of the preventive measures — as a guarantee of the respect for rights indispensable accused/defendant in criminal proceedings.Even if at first glance the law is clear and concise, however, judicial practice has passed different solutions, often giving the misinterpretation, and precisely why during the study I will present some of the most relevant solutions jurisprudenţiale, both published and unpublished, as well as the jurisprudence of the European Court of human rights, also commenting on his own option likely controversy.In view of these considerations in the present research wish to realize a complete documentation and jurisprudenţiala and doctrinara, trying to force through the comments made on the text of regulations and solutions given by courts to make a judgment necessary and useful to practitioners of law cases of cessation of the right to preventive measures.